2013
DOI: 10.1002/cncr.28437
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of significant worsening of patient‐reported fatigue over a 1‐month timeframe in ambulatory patients with common solid tumors

Abstract: Purpose Understanding the determinants of fatigue worsening may help distinguish between different fatigue phenotypes and inform clinical trial designs. Patients and Methods Patients with invasive cancer of the breast, prostate, colon/rectum, or lung were enrolled from multiple sites. At enrollment during an outpatient visit and 4–5 weeks later patients rated their symptoms on a 0–10 numerical rating scale. A 2-point change was considered clinically significant for fatigue change. Effects of demographic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
1
15
1
2
Order By: Relevance
“…Although previous research found that an increased number of comorbidities was associated with more severe fatigue, 47,61 in this study, neither the number nor the severity of comorbidities predicted enrollment levels or the trajectories of evening fatigue. These inconsistent findings may be explained by differences in the methods used to assess both fatigue (i.e., specific assessment of evening fatigue scores versus a mean fatigue score) and comorbidities (i.e., combined number and comorbidity severity score versus mean number of comorbidities).…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Although previous research found that an increased number of comorbidities was associated with more severe fatigue, 47,61 in this study, neither the number nor the severity of comorbidities predicted enrollment levels or the trajectories of evening fatigue. These inconsistent findings may be explained by differences in the methods used to assess both fatigue (i.e., specific assessment of evening fatigue scores versus a mean fatigue score) and comorbidities (i.e., combined number and comorbidity severity score versus mean number of comorbidities).…”
Section: Discussioncontrasting
confidence: 93%
“…2E) were the two clinical characteristics that predicted evening fatigue severity scores prior to the next dose of CTX. Consistent with previous reports that evaluated mean fatigue scores, 42,44,47 lower functional status was associated with higher evening fatigue scores. Functional status was not a predictor of evening fatigue in patients with breast 19 or prostate cancer 20 who received RT.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5,11-15 For example, patients who were younger, 5,11 female, 5 unmarried, 11 and with more education 13 reported higher fatigue severity. In other studies, patients who were employed, 16 had a higher stage of disease at diagnosis, 12 and those who reported more comorbidities 12,17 had higher fatigue severity scores during CTX. Across these studies, 5,11-17 inconsistencies were found in the predictors, which may be related to the timing of the fatigue assessments; the failure to examine demographic, clinical and symptom characteristics in the same patients longitudinally; and/or the failure to evaluate diurnal variations in fatigue severity.…”
Section: Introductionmentioning
confidence: 73%
“…This finding contrasts with prior studies with patients with mixed cancer diagnoses that identified patients with lung cancer as having higher levels of fatigue compared to other diagnoses. 12,15,17 A better understanding of the common and distinct molecular mechanisms that underlie the development of morning and evening fatigue may provide insights into how the unique and common predictors of diurnal variations in fatigue severity are interrelated. Across our two companion papers, common as well as unique characteristics were identified that were associated with initial levels as well as the trajectories of morning and evening fatigue.…”
Section: Discussionmentioning
confidence: 99%